COMPARISON OF TREATMENT OUTCOME OF SELF ADMINISTERED ANTI TUBERCULAR THERAPY WITH DIRECT OBSERVATIONAL THERAPY SHORT COURSE IN FEMALE GENITAL TUBERCULOSIS - S.P. JAISWAR,; AKANCHA PANDEY,; SWATI,; APALA PRIYADARSHINI, (International Journal of Pharma and Bio Sciences, 2016)
Female genital tuberculosis is responsible for damage of genital organ & a major cause of infertility and menstrual irregularities in developing countries like India. The present study was aimed to evaluate the comparison of treatment outcome of anti tubercular drugs given in the form of Self Administered Therapy (SAT) & Direct Observational Therapy (DOTS). Total 386 patients (223 for SAT group & 163 for DOTS group) were recruited from the OPD department of Obstetrics and Gynecology, KGMU, Lucknow, diagnosed FGTB. In 6 month treatment 130 (81.2%) patients cured in DOTS group, whereas only 81 (37.9%) cured in SAT group. P-value found 0.01 statistically significant for the DOTS group. A total 14 ADRs were found 3 (1%) SAT & 11 (7%) DOTS group patient respectively. Results showed that DOTS therapy better than the SAT & it helpful for the deprived socioeconomic patients.